PATHOGENETIC AND CLINICAL FEATURES OF ACUTE MYOCARDIAL INFARCTION IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - D. A. Alimov; R. P. Tulyakov; A. K. Ergashev; B. I. Shukurov (Modern American Journals, 2025)
This article examines the pathogenetic and clinical features of acute myocardial infarction (AMI) in patients with type 2 diabetes mellitus (T2DM), a condition associated with a higher incidence of complications, a more severe clinical course, and a poorer prognosis compared with patients without diabetes. AMI remains one of the leading causes of mortality among individuals with T2DM, with its incidence being 2–3 times higher than in the general population. Disturbances in carbohydrate metabolism, insulin resistance, systemic inflammation, hyperglycemia, and accelerated atherosclerosis contribute to atherosclerotic plaque instability and an increased risk of thrombosis. In patients with T2DM, AMI often presents with an atypical clinical course, characterized by reduced pain perception, a higher risk of recurrent myocardial infarction, cardiac arrhythmias, and the development of heart failure.
Keywords: Acute myocardial infarction; type 2 diabetes mellitus; pathogenesis; insulin resistance; acute heart failure; atherosclerosis; thrombosis.